MO093: Dietary Sodium Restriction Reduces Nocturnal Blood Pressure in Treatment Resistant Hypertensive Patients. (3rd May 2022) - Hornstrup, Bodil; Hoffmann-Petersen, Nikolai; Lauridsen, Thomas G; Nørgaard Bech, Jesper
Abstract: BACKGROUND AND AIMS: High blood pressure (BP) is an essential contributor to the risk of cardiovascular disease (CVD) and death. Hence, diagnosing and treating patients with high BP is paramount if the number of cardiovascular related death should be reduced. High nocturnal BP and blunting of normal nocturnal BP decrease have stronger correlation to the risk of CVD than high day time BP. Lowering nocturnal BP is assumed to reduce the risk of CVD. Patients with treatment resistant hypertension (TRH) represent a subgroup of hypertensive patients characterized by lack of BP control despite antihypertensive treatment. These patients are at particular risk of CVD and target organ damage. Patients with TRH are more likely to experience BP increase as a response to sodium loading than other individuals. Lifestyle modification is an important treatment angle in hypertensive patients. It is, in particular, central to reduce sodium intake, as high sodium intake increases the risk of TRH. Thus, in this study we aimed to analyse if self-performed dietary sodium restriction could be implemented in patients with TRH. Moreover, we aimed to analyse the effect of this attempted restriction on nocturnal BP and 24 h BP, on plasma levels of BNP and nitric oxide, and on body water content. METHOD: Patients with TRH from 20 to 70 years with normal renal function were invited for participation in this cross-over interventional study. Patients were screened with 24 h ambulatory BP monitoring initiated after observed intake of usual antihypertensive medication, and they were included if 24 h systolic BP/diastolic BP ≥ 130/80 mmHg. Study participation included two periods of 14 days; a standard period with usual diet and an interventional period with instructed dietary sodium restriction and handed-out sodium-reduced bread. For both periods, all antihypertensive medication was dosed and handed out and ingested in the morning. At the end of each period, patients were examined with 24 h BP monitoring, 24 h urine collection (sodium excretion), blood samples (nitric oxide and BNP) and bioimpedance measurement (body water content). RESULTS: Baseline characteristics of the fifteen included patients are shown in Table 1. Eleven of the patients were male. Patients had been treated for hypertension for a mean of 12.5 (7) years and excreted a mean of 11.2 grams of salt at baseline [192 (86) mmol sodium]. All patients but one reduced sodium excretion at follow up. Table 2 shows the effect of sodium restriction on BP, nitric oxide, BNP and body water content. Sodium excretion was reduced to 91 mmol/24 h, which equals 5.3 g of salt. BP (24 h, day and nocturnal) decreased significantly as well as body water content and plasma levels of BNP. These changes were, however, not correlated. Plasma levels of nitric oxide increased, but it was not related to the changes in BP. Nocturnal fraction of 24 h sodium excretion increased after sodium restriction; however, this was not correlated to changes in nocturnal BP. Renal function and urinary potassium excretion both remained unchanged. Four patients experienced side effects; three reported newly onset dizziness at follow-up; two of them had 24 h BP reduction > 10 mmHg systolic. One patient had increased creatinine and potassium at follow-up. CONCLUSION: In a population of 15 treatment resistant hypertensive patients, we demonstrated that self-performed dietary sodium restriction could be implemented. Urinary sodium excretion was reduced significantly to 5.3 g/24 h. Nocturnal BP was reduced significantly; dipping status was, however, unchanged. Increased plasma levels of nitric oxide may be evidence of improved endothelial function. Hence, by the local vasodilating effect, NO may be one of the involved mechanisms in BP decrease following a sodium restriction. Reduced extracellular water content and BNP may be other explainable effects of BP reduction after inducing sodium restriction.